2012
DOI: 10.1097/ajp.0b013e318227ce7a
|View full text |Cite
|
Sign up to set email alerts
|

Phantom Limb Pain in Young Cancer-related Amputees

Abstract: Objectives This study in children and young adults having cancer-related amputation aimed to examine the incidence of phantom limb pain in the first year after amputation and also the proportion of patients who had pre-amputation pain. Methods A retrospective review of medical records was undertaken. The proportion of patients with phantom limb pain was reported. Fisher’s exact test was used to examine the association between phantom limb pain and the presence of pre-amputation pain and between phantom limb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 10 publications
(13 reference statements)
0
30
0
Order By: Relevance
“…Our findings are consistent with those of the study by Krane et al which found that over a 10-year period, 90% of pediatric cancer–related amputations resulted in PLP 8 , and they are slightly higher than the findings of the study by Burgoyne et al, which reported that 76% of patients had PLP, and only 10% experienced PLP that persisted at 1 year post-amputation. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with those of the study by Krane et al which found that over a 10-year period, 90% of pediatric cancer–related amputations resulted in PLP 8 , and they are slightly higher than the findings of the study by Burgoyne et al, which reported that 76% of patients had PLP, and only 10% experienced PLP that persisted at 1 year post-amputation. 7 …”
Section: Discussionmentioning
confidence: 99%
“…7 The study evaluated factors to predict PLP, and although all patients who experienced PLP 1 year after amputation were older than 18 years, had pre-amputation pain, and had a proximal limb amputation, none of these factors were statically significant, possibly due to the small sample size. 7 Patients who undergo pediatric cancer–related amputations have a higher incidence of PLP (90%) than the pediatric amputation population as a whole (83%). 8 …”
Section: Introductionmentioning
confidence: 99%
“…For congenitally related amputations, the prevalence of PLP has been noted to be lower, between 3.7 and 20% of children, even occurring in children with congenital absence of a limb ( 4 , 10 ). In the pediatric oncology population, the prevalence of PLP is also wide ranging between 48 and 90% ( 5 , 7 , 11 , 12 ). The onset of pediatric PLP typically occurs shortly after amputation, most often within the first week after amputation ( 5 , 7 ).…”
Section: Pediatric Plp Characteristics and Epidemiologymentioning
confidence: 99%
“…Phantom limb pain may also be related to pre-amputation pain in pediatric populations, although results of this research have been mixed. Pre-amputation pain has been noted to be present in 35–90% of pediatric amputation patients ( 4 , 5 , 11 ). A recent study (2012), however, did not find a significant difference between the experience of pre-amputation pain and the development of PLP post-amputation ( 11 ).…”
Section: Pediatric Plp Characteristics and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation